The effect of rain on the turbidity of gravity feed water supply in remote villages in Marudi district in Sarawak - Mansoor, Faizul (2000)
Water is available as surface water, ground water and as rain. Although 97.2% of the 20 million population of Malaysia is provided with water, only the urban areas have treated water. The remote areas and rural villages are still without treated water In Sarawak, water supply to villages in remote and rural areas are made available through wells, water tanks, gravity feed supply and in certain areas, extension of the public water supply. Water that is contaminated, smelly and polluted are not accepted nor use by the people. In rural Sarawak, 57.2% of the total households of 109,605 persons has gravity feed (mountain water) supply as their source of drinking water. Although this water is safe for drinking, it is rejected when it becomes turbid. Three remote villages in Sarawak with gravity feed water supply is studied to show the effect of rain on the turbidity of the water supplies and how the turbidity affect their utilisation. In this study, it is found that the turbidity of water in these areas are increase during rain. It is also found that when the gravity feed water becomes turbid, it is not readily used for drinking or cooking but is used for other domestic purposes. The National Drinking Water Guidelines have set a standard of 5 NTU as the standard turbidity of water for drinking. This study shows this standard is exceeded. It is therefore recommended that the all the catchment areas where there are gravity feed supply be preserved and protected and its water be filtered and treated before use.